Structural fire engineering - LaMalva, Kevin J.; Structures Engineering Institute (American Society of Civil Engineers). Fire protection Committee (Reston, Virginia : American Society of Civil Engineers, 2018)
Structural Fire Engineering, MOP 138, is a valuable resource for practicing structural engineers, architects, building officials, and academics concerned with performance-based design for structural fire safety--
Includes bibliographical references and index.
H,B
Keywords: Building, Fireproof